First clinical multicenter experience with the new Scepter Mini microballoon catheter - Vollherbst, Dominik; Chapot, René; Wallocha, Marta; Saatci, Isil; Cekirge, Saruhan; Rouchaud, Aymeric; Mounayer, Charbel; Kocer, Naci; Kizilkilic, Osman; Sourour, Nader A.; Shotar, Eimad; Psychogios, Marios N.; et al. (Journal of neuroInterventional surgery, 2021)
Background Balloon-assisted techniques can improve the endovascular treatment of cerebrospinal vascular malformations. The aim of this study was to report the first clinical multicenter experience with the new Scepter Mini dual-lumen microballoon catheter. - Methods Patients with cerebral or spinal vascular malformations treated with the Scepter Mini at seven European neurovascular centers were retrospectively reviewed. Clinical data, angiographic features of the vascular malformations, procedural parameters including the type of application, navigability, technical failures, complications and embolization success were assessed. - Results The usage of 34 Scepter Mini microballoon catheters in 20 patients was analyzed. Most treated malformations (80.0%) were cerebral arteriovenous malformations. Four different applications were reported: embolization via Scepter Mini (n=23, 67.6%), balloon-occlusion with simultaneous embolization via a second microcatheter (n=3, 8.8%), diagnostic angiography with simultaneous balloon-inflation for flow arrest (n=4, 11.8%), and navigation support (n=4, 11.8%). The mean diameter of the blood vessels in which the Scepter Mini was inflated was 1.9±0.5 mm. The navigability of the Scepter Mini was rated as ‘easy’ or ‘very easy’ in 88.2% of cases. Complete occlusion of the malformation was achieved in 60.9% of cases. Technical failures occurred in 4/23 embolization procedures, and all were related to insufficient stability of the balloon within the vessel. No complications related to the Scepter Mini were observed, while unrelated complications occurred in three patients (15.0%). - Conclusions The Scepter Mini is a promising new device for balloon-assisted embolization of cerebrospinal vascular malformations via small feeders. Beyond embolization, the Scepter Mini can also be used for other applications, such as superselective flow arrest and navigation support.